Epigallocatechin-3-Gallate as a Novel Vaccine Adjuvant - Cheong, Yucheol; Kim, Minjin; Ahn, Jina; Oh, Hana; Lim, Jongkwan; Chae, Wonil; Yang, Seung Won; Kim, Min Seok; Yu, Ji Eun; Byun, Sanguine; Jang, Yo Han; Seong, Baik Lin (Frontiers in Immunology, 2021)
Vaccine adjuvants from natural resources have been utilized for enhancing vaccine efficacy against infectious diseases. This study examined the potential use of catechins, polyphenolic materials derived from green tea, as adjuvants for subunit and inactivated vaccines. Previously, catechins have been documented to have irreversible virucidal function, with the possible applicability in the inactivated viral vaccine platform. In a mouse model, the coadministration of epigallocatechin-3-gallate (EGCG) with influenza hemagglutinin (HA) antigens induced high levels of neutralizing antibodies, comparable to that induced by alum, providing complete protection against the lethal challenge. Adjuvant effects were observed for all types of HA antigens, including recombinant full-length HA and HA1 globular domain, and egg-derived inactivated split influenza vaccines. The combination of alum and EGCG further increased neutralizing (NT) antibody titers with the corresponding hemagglutination inhibition (HI) titers, demonstrating a dose-sparing effect. Remarkably, EGCG induced immunoglobulin isotype switching from IgG1 to IgG2a (approximately >64–700 fold increase), exerting a more balanced TH1/TH2 response compared to alum. The upregulation of IgG2a correlated with significant enhancement of antibody-dependent cellular cytotoxicity (ADCC) function (approximately 14 fold increase), providing a potent effector-mediated protection in addition to NT and HI. As the first report on a novel class of vaccine adjuvants with built-in virucidal activities, the results of this study will help improve the efficacy and safety of vaccines for pandemic preparedness.